Development of a new method to prepare nano-/microparticles loaded with extracts of azadirachta indica, their characterization and use in controlling plutella xylostella - Forim, Moacir Rossi; Costa, Eveline Soares; Da Silva, Maria Fátima Das Graças Fernandes; Fernandes, João Batista; Mondego, Janaina Marques; Boiça Junior, Arlindo Leal [UNESP] (American Chemical Society (ACS), 2013)
Biodegradable nanoparticles have been widely explored as carriers for controlled delivery of therapeutic molecules; however, studies describing the development of nanoparticles as carriers for biopesticide products are few. In this work, a new method to prepare nanoparticles loaded with neem (Azadirachta indica) extracts is presented. In this study, nanoparticles were formulated as colloidal suspension and (spray-dried) powder and characterized by evaluating pH, particle size, zeta potential, morphology, absolute recovery, and entrapment efficiency. A high-performance liquid chromatography method was used for nanoparticle characterization. The best formulations presented absolute recovery and entrapment efficiencies of approximately 100% and a release profile based on swelling and relaxation of the polymer or polymer erosion. The biological data of the formulated products against Plutella xylostella showed 100% larval mortality. The nanoparticle information improved the stability of neem products against ultraviolet radiation and increased their dispersion in the aqueous phase. © 2013 American Chemical Society.
Keywords: Azadirachta indica; nanoparticles; Plutella xylostella; spray-dried powders; stability